2005
DOI: 10.1002/chem.200400838
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Desulfitative Mizoroki–Heck Couplings of Sulfonyl Chlorides with Mono‐ and Disubstituted Olefins: Rhodium‐Catalyzed Desulfitative Heck‐Type Reactions under Phosphine‐ and Base‐Free Conditions

Abstract: New conditions have been found for the desulfitative Mizoroki-Heck arylation and trifluoromethylation of mono- and disubustituted olefins with arenesulfonyl and trifluoromethanesulfonyl chlorides. Thus (E)-1,2-disubstituted alkenes with high stereoselectivity and 1,1,2-disubstituted alkenes with 12:1 to 21:1 E/Z steroselectivity can be obtained. Herrmann's palladacycle at 0.1 mol % is sufficient to catalyze these reactions, for which electron-rich or electron-poor sulfonyl chlorides and alkenes are suitable. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(43 citation statements)
references
References 52 publications
1
40
0
2
Order By: Relevance
“…[252] Reaction between 4-chlorophenylsulfonyl chloride and styrene gave an impressive 60 % yield of the corresponding vinyl sulfone, demonstrating excellent selectivity over the aryl chloride bond, which agrees with the reported greater reactivity of sulfonyl chlorides towards oxidative addition compared with the analogous bromides and chlorides. [253,254] This indicated that there was reasonable precedent for the analogous Heck reaction between 4-bromophenylsulfonyl chloride 196 and acrylonitrile, but the desired product 200 was only isolated in only 5 % yield along with the sulfonic acid 201 in 3 % yield, Equation 12.…”
Section: Equation 11supporting
confidence: 82%
“…[252] Reaction between 4-chlorophenylsulfonyl chloride and styrene gave an impressive 60 % yield of the corresponding vinyl sulfone, demonstrating excellent selectivity over the aryl chloride bond, which agrees with the reported greater reactivity of sulfonyl chlorides towards oxidative addition compared with the analogous bromides and chlorides. [253,254] This indicated that there was reasonable precedent for the analogous Heck reaction between 4-bromophenylsulfonyl chloride 196 and acrylonitrile, but the desired product 200 was only isolated in only 5 % yield along with the sulfonic acid 201 in 3 % yield, Equation 12.…”
Section: Equation 11supporting
confidence: 82%
“…They have been used for more than a century in material sciences and medicinal chemistry. [18][19][20][21][22][23] Recently, we have shown that Stille, carbonylative Stille, 24,25 Suzuki-Miyaura, 26 Sonogashira-Hagihara 27 type cross-couplings and Mizoroki-Heck 28,29 type arylations can be carried out using sulfonyl chlorides as electrophilic partners under desulfinylation conditions. 30 In the case of Mizoroki-Heck coupling reaction, Pd nanoparticles in nitrile-functionalized ionic liquid, without expensive or toxic ligands can be used as recoverable catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The Pd 0 forms in the main catalytic cycle, after β-hydride and reductive elimination steps. [48] wileyonlinelibrary.com/journal/aoc The useful effects of tetrabutylammonium salts as additives or solvents in the Heck reaction have been known for a long time. [49] The co-catalytic effect of tetraalkylammonium salts has been assigned as phase-transfer catalysis and increased polarity of the solvent, which stabilizes ionic and polar transition states in the catalytic cycle and leads to an increase in the whole reaction rate.…”
Section: Resultsmentioning
confidence: 99%